2012
DOI: 10.1063/1.4754851
|View full text |Cite
|
Sign up to set email alerts
|

Origin of plasticity in ultrafine lamellar Ti-Fe-(Sn) composites

Abstract: Transmission electron microscopic studies of eutectic Ti68.38Fe28.61Sn3 upon 5% and 10% plastic deformation reveal slip transfer across the β-Ti/FeTi lamellae interface. Stroh's analysis suggests that addition of Sn to Ti70.5Fe29.5 increases the cleavage stress and reduces the slip stress around a dislocation pile-up at β-Ti/FeTi interface. The presence of ultrafine lamellar FeTi contributes strengthening whereas, dislocation slip is the origin of plasticity in high strength Ti-Fe-(Sn) composites

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Along this direction, Maity and Das has revealed that the dislocation-lamellae interaction improves the strength and the ultrafine lamellar phases contribute to strain-hardening during plastic deformation. Whereas, slip transfer across the lamellae interface improves the global plasticity in UECs, which has been also supported by the model calculations [31]. However, the effects of alloy addition and lamellar spacing on the deformation mechanism in homogeneous UEC, especially activation volume and strain rate sensitivity, have not been studied systematically.…”
Section: Introductionsupporting
confidence: 53%
See 3 more Smart Citations
“…Along this direction, Maity and Das has revealed that the dislocation-lamellae interaction improves the strength and the ultrafine lamellar phases contribute to strain-hardening during plastic deformation. Whereas, slip transfer across the lamellae interface improves the global plasticity in UECs, which has been also supported by the model calculations [31]. However, the effects of alloy addition and lamellar spacing on the deformation mechanism in homogeneous UEC, especially activation volume and strain rate sensitivity, have not been studied systematically.…”
Section: Introductionsupporting
confidence: 53%
“…In order to study the deformation behavior of the individual eutectic phases i.e. b-Ti and FeTi, single phase polycrystalline alloys with nominal compositions of Ti 80 Fe 20 , Ti 82 Fe 10 Sn 8 , and Ti 51.5 Fe 48.5 have been prepared according to our earlier reports [31]. These compositions have been schematically shown as dotted lines in binary TiFe alloy phase diagram, as illustrated in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, twins and stacking faults are observed throughout, with more stacking faults and micro-twins accumulated at the top section of nanowire. The streaky diffraction spots are likely caused by the Sb-induced strain resulting in planar defects [10]. Figure 8 shows the normalized photoluminescence (PL) spectra of nanowires at different shell growth temperatures.…”
Section: Resultsmentioning
confidence: 99%